Distinguishing Supportive Activities at Industry-Level Value Chain Analysis - Kim, Euisung; Han, Jieun; Kwon, Gyu-Hyun (International JOURNAL OF CONTENTS, 2023)
Although globalization gives us a more efficient product system, recent collapse of the Global Value Chain raises a severe problem for a company's sustainability. This study aimed to identify supportive activities of industry-level value chain using social network analysis. We used reported transaction data from a Koreancredit rating company in the investigation. By applying analysis of structural equivalence, we classified some companies in the transactional network. In addition, we identified the group classified as supportive activities in the industrial value chain using network parameters. This result will provide vital information to establish corporate-level strategies considering their industry-level value chain. Moreover, this result is a starting point to classify primary activities in the industry-level value chain accurately. KCI Citation Count: 0